2015
DOI: 10.1016/j.ajpath.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The Homeoprotein DLX4 Stimulates NF-κB Activation and CD44-Mediated Tumor–Mesothelial Cell Interactions in Ovarian Cancer

Abstract: Ovarian cancers often highly express inflammatory cytokines and form implants throughout the peritoneal cavity. However, the mechanisms that drive inflammatory signaling and peritoneal metastasis of ovarian cancer are poorly understood. We previously identified that high expression of DLX4, a transcription factor encoded by a homeobox gene, is associated with reduced survival of ovarian cancer patients. In this study, we identified that DLX4 stimulates attachment of ovarian tumor cells to peritoneal mesothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…It has been reported that CARD11 is elevated in epithelial ovarian cancer [ 29 ]. Other studies reinforce that the NF-κB pathway can be activated by CARD11 [ 30 , 31 ] and plays a metastatic-associated role in ovarian cancer via various regulatory factors such as CD44 [ 32 ]. These studies strongly suggest that CARD11 may play an oncogenic role similar to that of CTD-2020K17.1.…”
Section: Discussionmentioning
confidence: 84%
“…It has been reported that CARD11 is elevated in epithelial ovarian cancer [ 29 ]. Other studies reinforce that the NF-κB pathway can be activated by CARD11 [ 30 , 31 ] and plays a metastatic-associated role in ovarian cancer via various regulatory factors such as CD44 [ 32 ]. These studies strongly suggest that CARD11 may play an oncogenic role similar to that of CTD-2020K17.1.…”
Section: Discussionmentioning
confidence: 84%
“…The methylation of DLX4 was strongly associated with high risk of recurrence and poor prognostic survival in lung cancer patients [31]. The gene can drive tumor progression in ovarian cancer through the NF-κB pathway by activating a regulatory factor cell surface molecule CD44 [32]. It was also found to promote ovarian cancer by inducing the expression of iNOS, an enzyme that stimulates angiogenesis [33].…”
Section: Discussionmentioning
confidence: 99%
“…Tjhay et al, for instance, have shown that disseminated ovarian tumors in the peritoneum contain highly enriched CD44v6-positive cancer cells and an increased number of CD44v6-positive cancer cells in primary tumors was associated with a shortened overall survival in stage III-IV ovarian cancer [29]. In a xenograft model, Haria et al found that DLX4, a transcription factor encoded by a homeobox gene, induced expression of CD44 in ovarian tumor cells, and inhibition of CD44 abrogated the ability of DLX4 to stimulate tumormesothelial cell interactions [30]. The fact that CD44 drives inflammatory signaling in PC is also consistent with our finding of differential regulation of SERPINB3, associated with host-immune-response [31].…”
Section: Discussionmentioning
confidence: 99%